Bile Proteome in Health and Disease. Issue 1 (10th January 2014) - Farina, Annarita; Delhaye, Myriam; Lescuyer, Pierre; Dumonceau, Jean‐Marc
Abstract: The study of bile proteins could improve the understanding of physiological processes involved in the regulation of the hepato‐biliary system. Researchers have tried for years to investigate the bile proteome but, until recently, only a few tens of proteins were known. The advent of proteomics, availing of large‐scale analytical devices paired with potent bioinformatic resources, lately allowed the identification of thousands of proteins in bile. Nevertheless, the knowledge of their role in the hepato‐biliary system still represents almost a "blank page in the book of physiology." In this review, we first guide the reader through the historical phases of the analysis of bile protein content, emphasizing the recent progresses achieved through the use of proteomic techniques. Thereafter, we deeply explore the involvement of bile proteins in health and disease, with a particular focus on the discovery of biomarkers for biliary tract malignancies. © 2014 American Physiological Society. Compr Physiol 4:91‐108, 2014.